2022
DOI: 10.1111/mcn.13332
|View full text |Cite
|
Sign up to set email alerts
|

Content analysis of breast milk substitutes marketing on Chinese e‐commerce platforms

Abstract: China has the largest and fastest-growing breast milk substitutes (BMSs) market and a disproportionately low exclusive breastfeeding rate. Many BMS manufacturers have established Chinese e-commerce stores. This marketing is of concern as it is likely to undermine breastfeeding. This study aimed to identify:(1) the marketing themes and strategies used to promote BMSs on the Chinese BMSs e-commerce websites; (2) if and how digital BMSs marketing may deviate from the World Health Organization Code of Marketing of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 31 publications
(49 reference statements)
1
8
0
Order By: Relevance
“…For example, 41% of interviewed mothers in a study from Ethiopia reported that they had seen BMS advertising, and 74% of the violations reported occurring through TV promotions (Laillou et al, 2021). Promotion via parent magazines was highlighted in a study in Taiwan (Chen) and in a Chinese study "premiumization" and "nutrition and science" were the main marketing appeal strategies on the BMS companies' websites and e-commerce platforms studied (Han, 2020) | 7 of 14 about risks from improper use was reported in Uruguay (Alcaire et al, 2020). In a study in Ecuador, more than half of the BMS labels contained texts or images that idealized their use (Caicedo-Borrás et al, 2021).…”
Section: Iycf Companymentioning
confidence: 99%
“…For example, 41% of interviewed mothers in a study from Ethiopia reported that they had seen BMS advertising, and 74% of the violations reported occurring through TV promotions (Laillou et al, 2021). Promotion via parent magazines was highlighted in a study in Taiwan (Chen) and in a Chinese study "premiumization" and "nutrition and science" were the main marketing appeal strategies on the BMS companies' websites and e-commerce platforms studied (Han, 2020) | 7 of 14 about risks from improper use was reported in Uruguay (Alcaire et al, 2020). In a study in Ecuador, more than half of the BMS labels contained texts or images that idealized their use (Caicedo-Borrás et al, 2021).…”
Section: Iycf Companymentioning
confidence: 99%
“…The highest number of sources was identified in 2020, with six sources within the year ( Figure 2 ) [ 24 , 25 , 26 , 27 , 28 , 29 ]. Among the sources obtained, peer-reviewed papers ( n = 20) [ 25 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ] were the most frequent type, followed by official reports ( n = 4) [ 46 , 47 , 48 , 49 ], narrative review ( n = 1) [ 50 ], comments ( n = 1) [ 24 ], open access theses ( n = 1) [ 26 ] and conference abstracts ( n = 1) [ 51 ]. All of the sources included in this scoping review were published in English.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the sources included in this scoping review focused on a single country ( n = 23); the rest of the publications considered more than one country, with one of them including up to 53 countries [ 49 ]. Australia was the country with the highest number of studies ( n = 5) [ 31 , 35 , 41 , 45 , 50 ], followed by Canada ( n = 4) [ 24 , 30 , 40 , 42 ], the United Kingdom (UK) ( n = 3) [ 33 , 38 , 49 ], the Philippines ( n = 3) [ 30 , 46 , 48 ], New Zealand ( n = 3) [ 36 , 43 , 44 ], the United States of America (US) ( n = 3) [ 25 , 30 , 34 ], China ( n = 3) [ 26 , 30 , 46 ], Indonesia ( n = 3) [ 30 , 32 , 46 ], Thailand ( n = 3) [ 32 , 39 , 46 ], Mexico ( n = 2) [ 27 , 31 ], India ( n = 2) [ 40 , 46 ], Ireland ( n = 2) [ 47 , 49 ], Myanmar ( n = 2) [ 40 , 42 ], Vietnam ( n = 2) [ 40 , 42 ], and some other countries with only one source ( Figure 3 ). Based on this scoping review, a total of 81 countries have any published documents or reports related to methodologies for the monitoring of the digital marketing of BMS to parents or caregivers ( ...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations